The Sign and Symtoms of Acute Stress Disorder in Flood Victims - Era Sari; Mustikasari Mustikasari (Jurnal Ilmu Keperawatan Jiwa, 2020)
Flood disasters in Indonesia increased from 2014-2018 with a total of 659 cases. Flood disasters cause considerable psychological impact, one of which is Acute Stress Disorder or ASD. The psychological impact that was first experienced by a person affected by a flood when in a crisis situation is the emergence of panic and fear and loss. Disaster victims who began to realize that they experienced loss after the panic response experienced began to decline, and this causes many disaster victims to feel unprepared to accept the conditions of loss. The unpreparedness of this individual in accepting loss causes a sad response which is commonly known as grieving. some other people the process of grieving can increase, if not treated can develop into chronic grieving, causing a stress response that is characterized by dissociative symptoms after trauma called Acute Stress Disorder. The  objective to identity the sign and symtoms of acute stress disorder in flood victims. The method this type of research is cross sectional used  to ilusstrate or describe a phenomenon that is supported by the results of a visit, population all affected by flood victimsin the vilages of Talang Putri and Talang Bubuk in Palembang.  Data collection was carried out with interview and observation techniques related to signs and symptoms of Acute Stress Disorder. Field research results indicate that traumatic experiences in which psychological conditions (fear, panic, loss of grief, stress) experienced by a person. Apart from that disositive symptoms found also a decrease in the ability to express emotions, fixated, feeling this incident was a nightmare. which can increase the potential for experiencing ASD.